RELATIONSHIP BETWEEN RECURRENT LARYNGEAL NERVE (RLN) AND INFERIOR THYROID ARTERY (ITA) IN OUR POPULATION: Recurrent Laryngeal Nerve And Inferior Thyroid Artery - Ahmad, Maqbool; Ashraf, Imran; Sharif, Arslan (Pakistan Armed Forces Medical Journal, 2018)
Objective: To find out the relationship between recurrent laryngeal nerve(s) (RLN) and inferior thyroid artery (ITA) in patients undergoing thyroid surgery in our population. Study Design: Descriptive, cross-sectional study. Place and Duration of Study: Pak Emirates Military Hospital Rawalpindi and Combined Military Hospital Rawalpindi from Aug 2008 to Dec 2014. Material; and Methods: One hundred recurrent laryngeal nerves, 50 right and 50 left were studied in 64 patients. All cases of benign goiter, malignant T1, T2 goiter, completion thyroidectomy cases on virgin side were included. Malignant T3, T4 cases, redo surgery, and large multi nodular goiter, cases in which posterior nodules have displaced the nerve (s) were excluded from the study. The course of the nerve was dissected in the thyroid vicinity and its relation with the inferior thyroid artery was recorded and photographed. All the data and special points were noted by the surgeons themselves in a register in all the cases and photographs were also taken. The data was entered and analyzed using statistical package for social sciences (SPSS) version 16. A p-value of <0.05 was considered significant. Results: Hundred RLN were studied in 64 patients. In 36 patient RLN on both sides and in 14 patients the right and in 14 patients the left RLN were studied. The age ranged from 15-65 years with mean age 36.4 years. Male to female ratio was, 1: 4.3. Percentage of male patients was 18.75% as compared to female was 81.25%. In our study the nerve was more commonly found passing posterior to inferior thyroid artery on both sides and in both sexes. On the right side it was seen in 60% of cases and on the left side it was seen in 70% of the cases Conclusion: Relationship of RLN with ITA is variable in our population. The surgeon should be aware of these variations and meticulous dissection of RLN is mandatory in tumor surgery and redoes thyroid surgery to avoid injury to these nerves.